Creolization as cultural creativity - Baron, Robert A.; Cara, Ana C. (University Press of Mississippi, 2011)
This volume explores the expressive forms and performances that come into being when cultures encounter one another. Creolisation is presented as a powerful marker of identity in the post-colonial creole societies of Latin America, the Caribbean, and the southwest Indian Ocean region, as well as a universal process that can occur anywhere cultures come into contact. Drawing from the disciplines of folklore, anthropology, ethnomusicology, literary studies, history, and material culture studies, essayists address theoretical dimensions of creolisation and present in-depth field studies.